EFEKTIFITAS DAN PEMANFAATAN INSENTIF PAJAK PADA UMKM PADA MASA PANDEMI COVID-19 - Rayna Kartika; Iswardi (Jurnal Bisnis Terapan, 2022)
During pandemic Covid-19, the productivity of SME(small and medium enterprises) is getting decreasing and the government boosts the existence of SME by giving the incentive tax until December 2020 to tax payer. SMEs are hoped to utilize the incentive tax as it can assist SMEs in Indonesia. Therefore, the objectives of this research are to (1) investigate the understanding of SMEs about article 21 and the tax incentives, (2) explore how effective the socialization about tax incentives. The design of this research is a qualitative descriptive using online interview and questionnaires. Samples taken are 40 SMEs in West Sumatera using purposive sampling techniques. The results show that more than 50% of SMEs in this research has already understood about income tax article 21, and more than 40% of SMEs are also familiar with the tax incentive, however, related to socialization of tax incentive from authority party, SMEs hope to obtain more information either online or offline.